HUBUNGAN KEJADIAN STROKE BERULANG DENGAN KUALITAS HIDUP PENDERITA STROKE DI RSUD ARIFIN ACHMAD - Zesi Nurwitri Yanti; Wasisto " Utomo; Darwin " Karim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstrack Stroke is the cause of most often that resulted in disability. Disability experienced due to stroke it can affect the quality of life of someone. This study aims to know the correlation the incident stroke recurring with the quality of life of patients with stroke using the study design analitik with a comparative study conducted in retrospective. Method sampling using purposive sampling with 32 respondents. Measured used the questionnaire SS-QOL consisting of 12 domain with a total 75 items questions related to the quality of life of patients with stroke has done test validity and reliability with Chronbach Alpha 0,967. The result analyzed by using univariate analysis that show frequence’s distribution and bivariate analysis by using Paired Sample t-Test. The result of the study found p value (0,00) < α (0,05). It’s mean there’s correlation  the incident stroke recurring with the quality of life of patients with stroke. Based on the research, researchers suggested to the institution of health for can provide quality of health services to be able to prevent recurring stroke, so it can improve the quality of life of patients with stroke. Keyword: Stroke, stroke recurring, quality of life, SS-QOL